Surgical and Non Surgical Interventions in Adult Congenital Heart Disease: Our Experience from COHARD registry - Budi Yuli Setianto; Dyah Wulan Anggrahini (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Surgical and Non Surgical Interventions in Adult Congenital Heart Disease:Our Experience from COHARD registry